Status and implications of promise (wa’d) in contemporary Islamic banking - Abdullah, Nurdianawati Irwani (Emerald Group Publishing, 2010)
Wa’ad or promise refers to undertaking by one party to do or not to do certain actions in future. Unlike a normal contract or `aqd, the rules governing wa`ad are less stringent as it is merely a promise thus is not binding. Under Shari’ah, due to the unilateral nature of the promise, the details of it are not as carved in stone as any other contract. The details such as time of delivery, the price, terms of payment and goods specific description are not as strict as applied in other contracts. Because of its flexibility, the wa’ad is now being noticed as a key alternative in structuring a lot of substitute products of a conventional bank. It is expected that the contract will grow more prominent in the next few years as demand for easy and flexible products increased. This paper, therefore attempts to analyze the status of promise from both Islamic and common law perspectives. Some illustrations of contemporary financial products structured based on wa`ad principle are discussed to shed some lights in understanding the issues surrounded the practice.